Soil organic matter of Cambisols in Vitosha mountain, Bulgaria - HRISTOV, Biser; PAVLOV, Pavel; PETROVA, Kamelia; MALCHEVA, Boyka (Edelweiss Applied Science and Technology, 2024)
A complex of soil carbon properties was studied and a research was made about the content of soil organic matter and organic C. The surface A and Bw horizon of Cambisols were studied in order understand relations of soil organic content and composition. Sample soil profiles in the middle part of Vitosha Nature Park were taken under different type of trees. Higher amount of total carbon and free low-molecular humic acids were determined in the surface and in the cambic horizons. The amount of soil organic carbon is high – from 2.08 % to 5.44 % in the surface horizon. The fulvic-humic type of soil organic matter predominates in studied soil horizons. Similar to this most of the soil samples have ration C/N > 15 which is Mull humus. This type is commonly associated with temperate forest ecosystems, where deciduous trees shed their leaves annually, and contributing organic matter to the soil.